Extranodal Rosai–Dorfman Disease Presenting as a Mediastinal Mass with Pulmonary Artery Invasion. (12th April 2018) - Orr, Andrew R.; Lefler, Daniel; Deshpande, C.; Kumar, Pallavi
Abstract : Rosai–Dorfman disease (RDD) is a rare, nonmalignant disorder of histiocyte proliferation typically involving the cervical lymph nodes. However, a subset of patients with RDD will display extranodal manifestations that are highly variable in presentation, more challenging to diagnose, and less likely to spontaneously regress compared to nodal disease. While case reports of extranodal involvement in nearly every organ system exist, documented instances of mediastinal and pulmonary artery involvement are particularly rare. This study describes the case of a middle-aged woman presenting with new onset right heart failure who was found to have extranodal RDD in the form of a large mediastinal mass with invasion and occlusion of the main pulmonary arteries.